Identification and Characterization of Five BAHD Acyltransferases Involved in Hydroxycinnamoyl Ester Metabolism in Chicory - Legrand, Guillaume; Delporte, Marianne; Khelifi, Chahinez; Harant, Adeline; Vuylsteker, Christophe; Mörchen, Monika; Hance, Philippe; Hilbert, Jean-Louis; Gagneul, David (Frontiers in Plant Science, 2016)
Chicory (Cichorium intybus) accumulates caffeic acid esters with important significance for human health. In this study, we aim at a better understanding of the biochemical pathway of these bioactive compounds. Detailed metabolic analysis reveals that C. intybus predominantly accumulates caftaric and chicoric acids in leaves, whereas isochlorogenic acid (3,5-diCQA) was almost exclusively accumulated in roots. Chlorogenic acid (3-CQA) was equally distributed in all organs. Interestingly, distribution of the 4 compounds was related to leaf age. Induction with methyljasmonate (MeJA) of root cell suspension cultures results in an increase of 3-CQA and 3,5-diCQA contents. Expressed sequence tag libraries were screened using members of the BAHD family identified in arabidopsis and tobacco as baits. The full-length cDNAs of five genes were isolated. Predicted amino acid sequence analyses revealed typical features of BAHD family members. Biochemical characterization of the recombinant proteins expressed in Escherichia coli showed that 2 genes encode HCTs (hydroxycinnamoyl-CoA:shikimate/quinate hydroxycinnamoyltransferases, HCT1 and HCT2) whereas 3 genes encode HQTs (hydroxycinnamoyl-CoA:quinate hydroxycinnamoyltransferases, HQT1, HQT2 and HQT3). These results totally agreed with the phylogenetic analysis done with the predicted amino acid sequences. Quantitative real-time polymerase chain reaction analysis of gene expression indicated that HQT3, HCT1 and HCT2 might be more directly associated with CQA accumulation in cell culture in response to MeJA elicitation. Transient expression of HCT1 and HQT1 in tobacco resulted in a higher production of 3-CQA. All together these data confirm the involvement of functionally redundant genes in 3-CQA and related compound synthesis in the Asteraceae family.